Streptomyces sp. VITGV100: An endophyte from Lycopersicon esculentum as new source of indole type compounds. (December 2022) - P, Veilumuthu; T, Nagarajan; S, Sasikumar; R, Siva; S, Jose; Christopher, J. Godwin
Abstract: Streptomyces spp. Produce a wide range of antimicrobial, anticancer, antioxidant, immunosuppressant, antiviral, and antimalarial compounds. Their genome harbour a vast biosynthetic potential genes. Herein, Streptomyces sp. VITGV100 has been investigated for its ability to produce antimicrobial secondary metabolites. To this purpose, the whole genome of Streptomyces sp. VITGV100 was sequenced by the Illumina Nextseq 500 platform. The total genome size is 8.08 Mb. The biosynthetic gene clusters were analyzed using antiSMASH 6.0: Streptomyces sp. VITGV100 comprises thirty-five biosynthetic gene clusters, some of which are potentially involved in the synthesis of bioactive secondary metabolites. Based on phylogeny investigation by MEGA X 6.0, Streptomyces sp. VITGV100 is a novel strain, whereas comparative genome analysis showed that Streptomyces litmocidini NBRC 12792 is its closer strain with an ANI value of 78.93% and dDDH value of 25.4%. Gene ontology database analysis unveiled BGCs accountable for the synthesis of indole-type compounds such as 7-prenylisatin and 5-isoprenylindole-3-carboxylate β-D-glycosyl ester. Indole-based compounds were further detected following GC-MS analysis. As the crude extract of Streptomyces sp. VITGV100 exhibited a promising antimicrobial activity, further studies are aimed to get new insight into its secondary metabolites. Graphical abstract: Image 1 Highlights: Streptomyces VITGV100 biosynthetizes unique indole alkaloid-type compounds. AntiSMASH reveals 35 gene clusters involved in secondary metabolites biosynthesis. Indole clusters have been reported. GCMS data show the diversity in antimicrobial compounds.